Cyclic helium enrichment of natural gas in a column with glass microspheres - Dolgushev, Sergey Viktorovich; Fomin, Vasiliy Mikhaylovich (Computational Continuum Mechanics, 2008)
The numerical investigation has been carried out for steady-cyclic regimes of operation of a column containing glass microspheres and designed for gallium enrichment of natural gas. It has been found that the concentration of helium in a mixture may increase several times.